Oxidized-low density lipoprotein level among Organophosphates (OPs) pesticide exposed workers - Abdullah, Nor Zamzila; Ishaka, Aminu; Samsuddin, Niza; Mohd Rus, Razman (College of Pathologists, Academy of Medicine Malaysia, 2010)
Organophosphate (OP) is one of the widely used pesticides worldwide. It has been shown to induce oxidative stress in both animal and human. Oxidative stress may stimulate the oxidation of lipoprotein particularly the low density-lipoprotein (LDL) which is known to promote atherogenesis. PON1 is high density-lipoprotein (HDL) related enzyme which is recognized for its function to hydrolyze OPs into a relatively less toxic substance and prevent atherosclerosis by hydrolyzing oxidized-LDL (ox-LDL). Low PON1 activities were reported in OPs exposed individuals, while in different studies it was associated with a higher risk of coronary artery disease (CAD). However, a link between chronic OP exposure, PON1 activity and ox-LDL which is known for its contribution in the development of atherosclerosis has not yet been reported. The aim of this report was to compare the level of PON 1 activities and ox-LDL between workers who are exposed to OPs and the comparative non-exposed group. Methods: A cross sectional study was carried among 51 selected pesticides sprayers from 4 farms in Kuantan who fulfilled the criteria while 48 control subjects were selected based on matching process of age, ethnicity and income bracket. Serum samples were analyzed for ox-LDL by ELISA method while PON1 activities were determined spectrophotometrically after the hydrolysis of substrates paraoxon, phenylacetate and diazoxon. Results: A significantly lower diazoxonase activity and higher ox-LDL level (p<0.001) was observed among the OP exposed group. The PON1 to ox-LDL ratio which probably reflect the ability of PON1 to hydrolyze ox-LDL were also significantly lower (p<0.05) among the OPs exposed group. Conclusion: Our data demonstrated that the increased ox-LDL may result from the reduced serum antioxidant capacity of PON1 in OPs exposed individuals. This may contribute to the development of atherosclerosis. A larger scale study is required to confirm our observation.